Sovereign Wealth Fund (Swf) Institution: Roles And Challenges Of The Indonesia Investment Authority (Ina) - Vincent Guo; Rouli Anita Velentina (Jurnal Pendidikan Indonesia, 2025)
Sovereign Wealth Fund (SWF) is a term in the realm of finance that refers to a state-owned financing institution. One of the Sovereign Wealth Funds owned by the Indonesian government, the Indonesia Investment Authority (INA), has been operational since 2024. As a progressive step in the development of Sovereign Wealth Funds in Indonesia, INA can be considered successful as a state investment management institution that has attracted the attention of foreign investors. Since its establishment, INA has played a role in driving investments in infrastructure, transportation, logistics, digitalization, healthcare, food security, green energy, and sustainable development. The sectors funded by INA range from geothermal energy in the green energy sector, the Belawan terminal infrastructure project, until Plasma Derivative Drug Products in healthcare. However, INA’s success is also accompanied by challenges, such as securing prospective investors, balancing economic interests with sustainable developmental priorities, and the impact of the global economic slowdown on investor confidence. Additionally, regulatory challenges—including policy alignment and even jurisdictional conflicts with other government institutions—are critical concerns for INA’s future growth. This research attempts to elaborate on the role of INA in the development of the Indonesian economy and the challenges faced by INA as Indonesia’s Sovereign Wealth Fund.